Intervenciones textiles sobre la yanchama para la aplicación en la indumentaria. - Achote Bustillos, Mishel Carolina (2023)
In this research project, textile interventions are made in the yanchama for its implementation in clothing, in collaboration with the Waorani community located in Gareno. The purpose of the integrated work is the production of an intervened textile for the commercialization and elaboration of clothing accessories. In addition, to propose a new biodegradable textile in the country's textile industry. The study carried out allows to investigate the physical characteristics of the textile and the applicable interventions in the yanchama. The work is developed in different stages such as : problem statement, bibliographic research, context analysis, application of the methodology, planning and development of the proposal. The results of the analysis determined the interventions such as textile preparation, dyeing, printing, embroidery and pyrography to be applicable in the yanchama. In addition, the user needs trend textile designs used in textile through manipulations for incorporation into the market. Therefore, a catalog with the textile interventions applied in yanchama is proposed to make known its varied use. KEY WORDS : TEXTILE INTERVENTIONS, YANCHAMA, WAORAN